Kejahatan di Bidang Perbankan dan lemahnya Pengawasan Bank - -, Sugiaryo - (probank, 2011)
ABSTRACT The loose Bank supervision keeps the potency of crime in banking field to exits. Crime in banking field does harm a lot of people, because basically most of wealth managed by bank belongs to people. Effective supervision strategy that can be applied to minimalize crime in Banking such as: (1). In making regulation and policy must be oriented on observation result, involving experts and oriented on the market, (2). Bank supervision must be oriented on the risk and intensify and effectify supervision, (3). The role of Bank of Indonesia must be supervisor and sanction giver, (4). Law upholding must be srived for consistently and consequently so that it is able to minimalize moral hazard, (5). Supervision organization structure must be dynamic and oriented on the team work development, (6). Quality of supervision Human Resource must be on the basic of special skill. Keyword: crime, banking, bank supervision